Design of circular pad coupler of inductive power transfer for electric vehicle (EV) - Zaini, Syasya Azra; Yusoff, Siti Hajar; Abu Hanifah, Mohd Shahrin; Sulaiman, Erwan; Nanda, Nadia Nazieha; Badruhisham, Saidatul Haneen (IEEE, 2021)
The depletion in energy sources especially oil is among the crucial issues nowadays in Malaysia. Since the quantity of vehicles in Malaysia are increasing, the oil sources are not enough to accommodate all. Wireless charging of Electric Vehicle (EV) has been developed to solve this issue but it gives limited performance due to misalignment, air gap and power loss. Therefore, this project proposed three coil pair design of circular pad coupler for wireless charging of EV. These three pairs were tested for air gap and misalignment cases using simulation and experimental work to find the best coil pair which gives the highest efficiency of power transfer. To design the circular pad, three elements are required in this project which are circuit parameters, geometric properties and experimental work. At first, the circuit parameters are calculated using a specific equation to obtain the inductance value for primary and secondary coil at resonant frequency which is needed for the fabrication of coil process. The simulation for ideal case were done using NI Multisim software to prove the calculated circuit parameters. Then, the geometric properties were calculated and designed in JMAG Designer software. Before designing the circular coil, several geometric parameters like inner diameter, outer diameter and number of turns were set up and calculated. Here, the magnetic flux density and power transfer were observed and measured for each coil pair design. The limitation for this study is that the high cost of copper wire and limited equipment in the laboratory.